Pengembangan Media Pembelajaran Interaktif Berbasis Augmented Reality untuk Meningkatkan Motivasi Belajar Matematika Siswa Kelas V di Madrasah Ibtidaiyah - Mutmainah, Mutmainah; Purwowidodo, Agus (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The development of interactive learning media based on Augmented Reality was carried out with the aim of increasing the mathematics learning motivation of madrasah ibtidaiyah students. This interactive learning media was developed according to the digital era which makes Augmented Reality learning media effective, interesting and fun. Development research using the ADDIE procedure modified into five development stages has produced a learning media product in the form of interactive learning media based on Augmented Reality with mathematical material in the form of educational game learning media. The results of the analysis of the collected data have shown differences in the development of mathematics learning motivation in students between before and after using learning media. Augmented reality-based interactive learning media has been developed in accordance with the independent curriculum, so that it can improve learning outcomes for students.